Каталитические свойства веществ: Справочник - Бакуменко Т. Т. Тамара Тимофеевна; Белая А. А. Алла Александровна; Вольфсон В. Я. Вадим Яковлевич; Гершингорина А. В. Алла Вениаминовна; Голодец Г. И. Григорий Израилевич; Гончарук В. В. Владислав Владимирович; Ройтер В. А. Владимир Андреевич (Киев, Наукова думка, 1968-)
Авт. указ. на обороте тит. л.